O.S.C.E. 1975-2015. 40 Years of Peaceful Conflict Resolution - Daniel Burlacu (CES Working Papers, 2016)
The European Union, in light of developments in the field of crisis-management concepts, is still in the phase of institutional building and foundation of its own concepts and doctrines. This does not mean that the EU has taken important steps towards the creation of a doctrine based on a crystallized concept of crisis management. It should be noted at this point that since 2004 the EU has defined a comprehensive approach to crisis management. However, although conceptually placed one step ahead of NATO's comprehensive approach, operational in concept, its actual implementation has proved to be a slow and difficult process for the EU because the EU does not have a military component of its own, being much more focused on the civilian crisis management component as part of its comprehensive approach and on the idea of cooperative security, where the EU has managed to become a major player in the area of strategic interest on the global scene.
Keywords: 330; O.S.C.E.; crisis management